Halamphora coffeaeformis: a source of lipids for biodiesel and value-added co-products - Scodelaro Bilbao, Paola Gabriela (2016)
Recent studies have indicated that the sustainable production of biodiesel from microalgae requires the use of a biorefinery approach. In the present work, Halamphora coffeaeformis, a marine benthic diatom native from Bahía Blanca Estuary, was cultured in order to evaluate the simultaneous production of triacylglycerols (TAG) for biodiesel and value-added co-products. For this end, the species was grown in a raceway pond in f/2 medium without the addition of vitamins. Total lipid content was 25.2% (dry weight (dw) and neutral lipids represented the 86%. Coincidently, TAG content was 17% (dw). Palmitoleic (26%), eicosapentanoic (23.6%) and palmitic (16.9%) fatty acids were the main components of the neutral lipid fraction, suggesting that H. coffeaeformis oil meets biodiesel standards. In addition, phytosterols were present at 0.22% (dw) while proteins represented 18.5% (dw). Finally, as the cell wall of H. coffeaeformis contains mainly silica, its amount was analyzed in the residue obtained after the lipid extraction. Results revealed that H. coffeaeformis contains 25% (dw) of silica. These findings provide baseline information and are the starting point for future scaling-up of this species under a biorefinery approach.